(untitled) - Li, Maozhen (Hoboken, NJ, 2005)
Find out which technologies enable the Grid and how to employ them successfully! This invaluable text provides a complete, clear, systematic, and practical understanding of the technologies that enable the Grid. The authors outline all the components necessary to create a Grid infrastructure that enables support for a range of wide-area distributed applications. The Grid: Core Technologies takes a pragmatic approach with numerous practical examples of software in context. It describes the middleware components of the Grid step-by-step, and gives hands-on advice on designing and building a Grid environment with the Globus Toolkit, as well as writing applications.
Keywords: Computational grids (Computer systems),Electronic data processing,Tính toán lưới (Hệ thống máy tính),Xử lý dữ liệu điện tử; Distributed processing,Xử lý phân bố